Identificação e caracterização molecular do vírus dengue em indivíduos sintomáticos atendidos na rede pública de saúde de Goiânia – Goiás, durante o período epidêmico 2012-2013 - Guimarães, Vanessa Neiva (2014)
Dengue is a major challenge to public health in Brazil and worldwide. Dengue virus (DENV) is an arbovirus of the family Flaviviridae, genus Flavivirus, classified into four antigenically distinct serotypes DENV1-4. Since the introduction of DENV1 in Goiás, the current situation consisted of successive epidemics of dengue fever with change among prevalence serotypes. One of the factors that have been associated with the pathogenesis of this infection is the occurrence of a cross-serotype immune response in secondary infections. Thus, the identification of circulating serotypes and also the characterization of the genomic variants have been considered important on disease surveillance, since the introduction of new variants can be a risk factor for severe dengue. In this context, the present study aimed to investigate the occurrence of DENV infection in individuals treated at health centers in Goiânia, Goiás in the epidemic period 2012-2013, using serological and molecular methods for determining the rate of positivity and identification of serotypes/genotypes in the circulating virus. For this, 278 samples from suspected individuals of DENV infection, which were submitted to the research of serological markers NS1, IgM and IgG using a commercial kit, as well as viral RNA detection and serotype identification by RT-PCR for region C-prM. The positivity for infection was 43.9%, with rates of 30.5%, 13.6% and 20.5% for NS1, IgM and RNA, respectively. Considering the RNA-positive samples, 31.5% were DENV1 and 68,5% were DENV4, which were subjected to nucleotide sequencing of the E/NS1 junction to characterize the viral genotype. Phylogenetic analysis classified the DENV1 samples as genotype V, that differentiated into two clades, which may reflect the occurrence of genetic variants with differences in evolutionary history. For DENV4 samples, classified as genotype II, was observed a phylogenetic proximity between the strains analyzed and others strains of the country and Latin America. These results demonstrate the effectiveness of the combination methods in the diagnosis of DENV infection. Still, the molecular evaluation has proven crucial to establish a complete data base to be used for surveillance studies, collaborating with investigations of the dynamics of the virus and the expected profile for future epidemics.